Qui accouche qui ? Etude de 134 récits d’accouchement à domicile - Geneviève Pruvost (Genre, Sexualité et Société)
At the intersection of the sociology of work, of professions and of gender, this article is based on the systematic study of 134 homebirth stories and asks whether and how do parturient take control of their own delivery in the case of homebirths? After presenting the context in which these narratives take place as well the sociodemographic profile of the storytellers, we will turn ourselves to the process by which family and professional hierarchies are inverted in favor of parturient women who are subtly empowered in the course of the delivery. However this empowerment does not lead to a unilateral magnification of female power. Stories show that the delivery is a collective labor and piece of work, that can generate new kinds of relationships.